Generalized and open selection approaches for the population mean: accounting for non-response and measurement error in single-phase sampling - Muhammad Sajjad; Muhammad Ismail; Atta-ur-Rahman; Amjad Rehman; Tariq Mahmood (Journal of Statistical Theory and Applications (JSTA))
Abstract In this paper, we have proposed a generalized estimator designed to estimate the mean of a finite population. The proposed estimator takes into account both instances of non-response and measurement error within the context of simple random sampling. The mean squared error (MSE) expression of the proposed estimator has been obtained, and the expression is approximated to the first order to provide insights into its characteristics. In a theoretical context, substantial evidence has been presented to demonstrate the superior efficiency of the proposed estimator when compared to certain pre-existing estimators. A comprehensive numerical study has been undertaken to further substantiate these theoretical findings. By comparing the empirical MSE values of the proposed estimator with their competing counterparts, a comprehensive understanding of its efficacy is obtained.